Arranging the Chairs in the Beloved Community The Politics, Problems, and Prospects of Multi-Racial Congregations in 1 Corinthians and Today - Rhodes, Michael J. (2020)
If racism is America’s original sin, it is also one of America’s most pressing contemporary problems. Indeed, Edwards’ recent research suggests that even intentionally multi-racial congregations often reproduce and reinforce white hegemony rather than undermine it. In this article, I first bring Edwards’ sociological research into dialogue with the theological critiques of racism within the ecclesia raised by Jennings and Sanders. I then offer a theological interpretation of 1 Corinthians 11:17-12:26 from the social location of American multi-racial churches subject to and complicit with racism for the purpose of those churches’ missional embodiment of an alternative politics. I argue that Paul critiques the church for gathering in ways more Corinthian than Christian. The solution is for the church to rearrange its communal life together in line with the eschatological ‘logic of the cross’. Such a cruciform community affords greater honor within the ecclesia precisely to those who lack it in the broader culture. In the concluding section, I consider how contemporary multi-racial churches might live out this ‘militant, reconciling ecclesiology’ today.
Keywords: 1 Corinthians; Cheryl Sanders; Eucharist; Korie Edwards; Willie James Jennings; Ecclesial Ethics; multi-racial congregations; Political Theology; Racism; Virtue Ethics